Vibration Reduction Effect of Steel Spring Floating Slabs under Water Immersion Conditions - YUAN Dehao; ZHANG Hongliang; YANG Lin; ZHOU Yu; NIU Xiaoli (Chengshi guidao jiaotong yanjiu)
［Objective］To address the issues of reduced vibration isolation performance of floating slabs under water immersion, it is necessary to study the impact of train operating speed and steel spring isolator stiffness on vibration reduction under operational conditions. ［Method］Based on fluid-structure interaction theory, a floating slab-immersion-tunnel fluid structure coupled vibration model is developed, incorporating the water-immersed steel spring floating slab and the tunnel. The accuracy of the model is validated using field data. The isolator stiffness and train speed affecting the vibration reduction performance of the water-immersed floating slab under train load action is analyzed. ［Result & Conclusion］Under steel spring floating slab water immersion conditions, changes in isolator stiffness and train operating speed primarily affect the amplitude of tunnel wall vibration, with minimal impact on the distribution of the dominant frequencies. As the stiffness of the steel spring isolators increases or the train operating speed rises, the vibration reduction performance of the floating slab deteriorates more significantly when immersed. When the water depth increases from 80 mm to over 160 mm (the immersion reaches from 1/4 to 1/2 of the slab side space height), the maximum Z-vibration level of the tunnel wall increases by over 10%. When the train operating speed decreases from 80 km/h to 40 km/h under floating slab water immersion conditions, the maximum vibration level of the tunnel wall decreases by approximately 8%, though it remains higher than that under non-immersed conditions. Once the water height exceeds 1/2 of the slab side space height, further reducing isolator stiffness or train operating speed is limited in improving vibration reduction performance.